A wearable chemical–electrophysiological hybrid biosensing system for real-time health and fitness monitoring - Imani, Somayeh; Bandodkar, Amay J.; Mohan, A. M. Vinu; Kumar, Rajan; Yu, Shengfei; Wang, Joseph; Mercier, Patrick P. (Nature communications, 2016)
Flexible, wearable sensing devices can yield important information about the underlying physiology of a human subject for applications in real-time health and fitness monitoring. Despite significant progress in the fabrication of flexible biosensors that naturally comply with the epidermis, most designs measure only a small number of physical or electrophysiological parameters, and neglect the rich chemical information available from biomarkers. Here, we introduce a skin-worn wearable hybrid sensing system that offers simultaneous real-time monitoring of a biochemical (lactate) and an electrophysiological signal (electrocardiogram), for more comprehensive fitness monitoring than from physical or electrophysiological sensors alone. The two sensing modalities, comprising a three-electrode amperometric lactate biosensor and a bipolar electrocardiogram sensor, are co-fabricated on a flexible substrate and mounted on the skin. Human experiments reveal that physiochemistry and electrophysiology can be measured simultaneously with negligible cross-talk, enabling a new class of hybrid sensing devices. Wearable sensors can provide continuous, convenient feedback for users but typically focus on a small number of physiological parameters. Here, the authors report a skin-worn sensing system that combines a biosensor for lactate detection with an electrocardiogram in one patch, with applications for exercise monitoring.